A Study on the Responses Effect of the Flow Field and Temperature on Hybrid Micro-Channel Heat Sink (H-MCHS) - Truong, Thi Kim Chi; Dang, Hung Son; Nguyen, Thi Anh Tuyet (Journal of Technical Education Science, 2023)
Research on the microchannel and its flow and heat transfer properties has received much attention. This study employed Autodesk Inventor software to build the model, and the Computational Fluid Dynamics software (Ansys Fluent 14) was used for numerical simulation. Taguchi analysis methods, ANOVA, and Minitab statistics testing were used. The results obtained for single response analysis for temperature, pressure, and velocity values are reasonable. With the optimal model for temperature difference () being W2H1S2 and the temperature difference across the model (), the pressure difference across the model (), maximum velocity in the channel (), and maximum outlet velocity () are W3H1S3, W1H1S3, W3H2S1, and W1H1S2, respectively. The analysis results for multi-response between the two values of velocity and pressure also achieved reasonable results with precisely defined parameters with response optimization for and , and the optimal model achieved is W(0.8mm), H(0.3mm), S(2.91), W(0.4mm), H (0.3mm), S(1.67), respectively. Analysis for , , , , and , the results are W(0.65mm), H(0.3mm), S(1), and W(0.4mm), H(0.3mm), S(1).